2018
DOI: 10.1016/j.pbiomolbio.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of blood flow on cardiac development

Abstract: The role of hemodynamics in cardiovascular development is not well understood. Indeed, it would be remarkable if it were, given the dauntingly complex array of intricately synchronized genetic, molecular, mechanical, and environmental factors at play. However, with congenital heart defects affecting around 1 in 100 human births, and numerous studies pointing to hemodynamics as a factor in cardiovascular morphogenesis, this is not an area in which we can afford to remain in the dark. This review seeks to presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 126 publications
(218 reference statements)
0
37
0
1
Order By: Relevance
“…Heart dilation has been seen in humans subsequent to a previous diagnosis of a hypertrophic heart, suggesting the heart is failing (Hamada et al ). Conversely, the developing or postnatal heart with a complex congenital defect (having two or more heart defects) is prone to abnormal haemodynamics, with a dilated heart seen as a secondary effect in some cases (Sanchez‐Gomez et al ; Courchaine et al ). In addition, a recent study has indicated that as heart development progresses (HH22 to HH36), the proximal part of the OFT (conus) becomes part of the right myocardial wall (Lazzarini et al ); this process could rescue the right ventricular wall from a dilating phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Heart dilation has been seen in humans subsequent to a previous diagnosis of a hypertrophic heart, suggesting the heart is failing (Hamada et al ). Conversely, the developing or postnatal heart with a complex congenital defect (having two or more heart defects) is prone to abnormal haemodynamics, with a dilated heart seen as a secondary effect in some cases (Sanchez‐Gomez et al ; Courchaine et al ). In addition, a recent study has indicated that as heart development progresses (HH22 to HH36), the proximal part of the OFT (conus) becomes part of the right myocardial wall (Lazzarini et al ); this process could rescue the right ventricular wall from a dilating phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, the most recent models identify shear stresses at the node surface as drivers of local exocytic release of morphogens, thus directly implicating fluid mechanics (Solowiej-Wedderburn et al, 2019). Clear effects of shear stresses have additionally been described later in development, especially in the maturation and differentiation of vascular cell types (Courchaine et al, 2018;Hwa et al, 2017). When not flowing, embryonic fluids exert pressures, and these, too, have been implicated in multiple steps of early development (Navis and Bagnat, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Comments on the significance of the CJ for the mechanical pump action of the early embryonic heart tube are also missed in contemporary monographs and textbooks on cardiac development [32,33]. Proper pumping function of the tubular embryonic heart is crucial for survival of higher vertebrate embryos as well as for correct morphogenesis of their hearts [34,35].…”
Section: Introductionmentioning
confidence: 99%